Eksplorasi Manajemen Privasi Komunikasi Mahasiswa Melalui Buku Harian Dan Instagram - Sahan, Meylisa Yuliastuti; Gual, Yoseph Andreas; Bello, Maria Florencia Yunita (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Internet-based social media platforms, such as Instagram, provide users with new spaces for self-expression, often blurring the boundaries of personal privacy. Before the digital era, personal diaries served as private outlets for emotional expression and self-reflection. This study explores how university students manage privacy boundaries when disclosing personal information through both digital (Instagram) and traditional (diary) media. Using Communication Privacy Management Theory as the analytical framework, this qualitative research involved document analysis of student diaries and in-depth interviews with ten Communication Science students. The results indicate three distinct privacy strategies: (1) those who use diaries exclusively for emotional release, (2) those who prefer Instagram’s “close friends” feature for semi-private sharing, and (3) those who selectively switch between both platforms based on content sensitivity. The study highlights the role of media characteristics in shaping privacy decisions and underscores the importance of digital literacy in navigating personal boundaries in a connected world.